Mission in the Nineteen 90s - Areeplackal, Pius (Journal of Dharma, 1992)
G,H, Anderson, J.M. Philips, R.C. Coote (ed.), Mission in the Nineteen 90s, Grand Rapids, Michigan: Wm. B. Eerdmans, 1991, pp. 80